2019
DOI: 10.1016/j.jor.2019.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Long – Term survivorship and clinical and radiological follow – up of the primary uncemented Delta III reverse shoulder prosthesis

Abstract: Background: Purpose of this study was to evaluate the longterm survivorship and clinical and radiological results of a primary reverse total shoulder arthroplasty (RTSA) performed with uncemented stems. Methods: From 2001 until 2006 61 primary uncemented RTSAs were implanted, which were included in a Kaplan-Meier survival analysis. Range of motion, functional scores and radiological followup was obtained. 27 patients were available for followup. Mean follow-up was 9.2 years (SD 2.4). Results: Mean cumulative s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 33 publications
2
4
0
2
Order By: Relevance
“…Second, the revision rate in this study (4.7%) was lower than that reported for similar prostheses both over comparable (7.3–25%) and longer follow-up periods (45%) [ 7 , 24 , 27 ]. Lastly, the patients in this study had high midterm implant survival rates that were within the range of recently published reports [ 25 , 28 ].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Second, the revision rate in this study (4.7%) was lower than that reported for similar prostheses both over comparable (7.3–25%) and longer follow-up periods (45%) [ 7 , 24 , 27 ]. Lastly, the patients in this study had high midterm implant survival rates that were within the range of recently published reports [ 25 , 28 ].…”
Section: Discussionsupporting
confidence: 83%
“…Second, the revision rate in this study (4.7%) was lower than that reported for similar prostheses both over comparable (7.3-25%) and longer follow-up periods (45%) [7,24,27]. Lastly, the patients in this study had high midterm implant survival rates that were within the range of recently published reports [25,28]. This study's main strengths were its midterm follow-up and multicenter setup using a reverse shoulder prosthesis with a soft-on-hard bearing couple.…”
Section: Discussionsupporting
confidence: 63%
“…One can expect that the low revision rate of 2.5% in the rTSA group will increase over time. Van Ochten et al reported long-term results of reversed shoulder arthroplasty with a revision rate of 8.2% after 9 years [34]. Although this is a substantial increase, the long-term revision rate of plate fixation is still considerably higher [35].…”
Section: Discussionmentioning
confidence: 99%
“…For determination of risk of bias, the Risk Of Bias In Non-Randomized Studies -of Interventions tool by Cochrane was used for non-Randomized Controlled Trials (RCTs) and the Risk Of Bias 2 tool for RCTs. 51,52 Both authors one and 2 assessed risk of bias, and in case of disagreement, author 5 and 6 were consulted. A more intense rehabilitation protocol was defined as a confounder and BIO and glenoid grafting as cointerventions.…”
Section: Risk Of Biasmentioning
confidence: 99%